Landau singularities from the amplituhedron - T. Dennen; I. Prlina; M. Spradlin; S. Stanojevic; A. Volovich (Journal of High Energy Physics, 2017)
Abstract We propose a simple geometric algorithm for determining the complete set of branch points of amplitudes in planar N $$ \mathcal{N} $$ = 4 super-Yang-Mills theory directly from the amplituhedron, without resorting to any particular representation in terms of local Feynman integrals. This represents a step towards translating integrands directly into integrals. In particular, the algorithm provides information about the symbol alphabets of general amplitudes. We illustrate the algorithm applied to the one- and two-loop MHV amplitudes.